From car use reduction to ride‐sharing: The relevance of moral and environmental identity. Issue 2 (24th June 2022) - Culiberg, Barbara; Cho, Hichang; Kos Koklic, Mateja; Zabkar, Vesna
Abstract: Car use contributes significantly to environmental pollution, leading people to rethink their transport habits. Previous studies on car use reduction relied on established theories related to values and self‐regulation to examine this decision. In this paper, we offer an alternative approach and examine the intention to reduce car use through the prism of identity theory, and propose environmental and moral identities, together with environmental concern, as the main antecedents to the importance of car use reduction and intention to reduce car use. Further, we consider ride‐sharing intention as an outcome of the decision to reduce car use. The proposed conceptual model is tested on a sample of consumers from the United Kingdom using an online consumer panel. The results offer partial support for the influence of moral identity, environmental identity, and environmental concern on the importance to reduce car use and intention. The links among the importance of and intention to reduce car use, along with ride‐sharing intentions, are supported. Finally, managerial implications are discussed, and future research directions are suggested.